Polychaete invader enhances resource utilization in a species-poor system - Karlson, Agnes M. L. (Springer-Verlag, 2011)
Ecosystem consequences of biodiversity change are often studied from a species loss perspective, while the effects of invasive species on ecosystem functions are rarely quantified. In this experimental study, we used isotope tracers to measure the incorporation and burial of carbon and nitrogen from a simulated spring phytoplankton bloom by communities of one to four species of deposit-feeding macrofauna found in the species-poor Baltic Sea. The recently invading polychaete Marenzelleria arctia, which has spread throughout the Baltic Sea, grows more rapidly than the native species Monoporeia affinis, Pontoporeia femorata (both amphipods) and Macoma balthica (a bivalve), resulting in higher biomass increase (biomass production) in treatments including the polychaete. Marenzelleria incorporated and buried bloom material at rates similar to the native species. Multi-species treatments generally had higher isotope incorporation, indicative of utilization of bloom material, than expected from monoculture yields of the respective species. The mechanism behind this observed over-yielding was mainly niche complementarity in utilization of the bloom input, and was more evident in communities including the invader. In contrast, multi-species treatments had generally lower biomass increase than expected. This contrasting pattern suggests that there is little overlap in resource use of freshly deposited bloom material between Marenzelleria and the native species but it is likely that interference competition acts to dampen resulting community biomass. In conclusion, an invasive species can enhance incorporation and burial of organic matter from settled phytoplankton blooms, two processes fundamental for marine productivity.